Investigating the sensitivity of microbubble acoustic response for biosensing applications - Harfield, C; Memoli, G; Jones, P; Ovenden, N; Stride, E (2013)
Microbubbles are currently used as contrast agents for diagnostic imaging on account of their high scattering efficiency and non-linear response to ultrasound. The exact nature of this response depends not only upon the bubble size and imposed sound field but also the bubble environment: physical properties of the surrounding liquid, bubble surface coating, ambient temperature, pressure and proximity to other bubbles or surfaces. This dependence can potentially be exploited for the microscale interrogation of a liquid to detect, e.g. changes in viscosity or the presence of particular chemical species. To facilitate this, the sensitivity of the microbubble acoustic response to changes in its environment must be analysed. The aim of this study was to provide a theoretical framework for this. A modified Rayleigh-Plesset equation was derived to describe the radial bubble motion, including the effects of gas diffusion and adsorption/desorption of a surfactant coating, and coupled to an equation describing microbubble translation. The presence of a rigid boundary was also included in the simulations. A sensitivity analysis was performed for the effect of each of the physical variables upon the bubble response, which indicated high sensitivity to species altering the dynamic surface tension and proximity to a boundary. © 2013 Acoustical Society of America.